Cell immobilization of Streptomyces griseobrunneus by microcrystalline cellulose for production of cyclodextrin glucanotransferase enzyme. Issue 1 (1st January 2021) - Afzali, Elham; Eslaminejad, Touba; Amirheidari, Bagher; Ansari, Mehdi
Abstract: The cyclodextrin glucanotransferase are extracellular enzymes that can hydrolysis starch as a substrate to cyclodextrin. Encapsulation and immobilization technique of microbial cells within the polymeric network have widespread applications in the production of enzyme. Bacterial cells were isolated from soil by serial dilution method. The molecular identity was established using 16S rDNA sequence analysis, and the identified strain was immobilized in the synthesized composites. Physicochemical characteristics of the synthesized composites were determined by using field emission scanning electron microscopy, Malvern Zetasizer Nano ZS and FT-IR analyses. Enzyme activity was measured by phenolphthalein assay. Streptomyces griseobrunneus was identified according to the 16S rDNA sequence. FT-IR analyses indicated that there was an interaction between all of the elements. Scanning electron microscopy analysis showed a cross-section of composites without cells and cells attached to composites. Enzyme activity was 1109, 948 and 606 U/ml in alginate/chitosan/microcrystalline cellulose (MCC) sheets, agar/gelatin/MCC beads and free cells, respectively. It could be concluded that the polymeric immobilization was effective in improving enzyme production because of its excellent properties such as guarding the bacterial cells against inhibitors and toxins.